Sodium bicarbonate and beta-alanine supplementation: Is combining both better than either alone? A systematic review and meta-analysis - Curran-Bowen, Terence; Guedes da Silva, André; Barreto, Gabriel; Buckley, John; Saunders, Bryan (Biology of Sport, 2024)
This systematic review and meta-analysis aimed to determine the effect of combined beta alanine (BA) and sodium bicarbonate (SB) supplementation on exercise capacity and performance. Four databases (PubMed, SPORTDiscus, Web Of Science and MEDLINE) were searched using relevant terms for studies involving healthy (e.g. no chronic diseases or conditions) male or female adults of any training status (athletes, physically active and nonathletes) and that investigated BA and SB in isolation and combination at any dose on an exercise outcome. Ten studies, totalling 243 individuals, met the criteria with 12 outcomes for each nutritional supplement. No ergogenic effect was detected in this meta-analysis for BA (SMD = 0.18, 95% CI: -0.06; 0.43, p = 0.13, tau² = 0, tau = 0, I² = 0.0%) or SB (SMD = 0.17, 95% CI: -0.08; 0.41, p = 0.16, tau² = 0, tau = 0, I² = 0.0%) in isolation. However, there was a beneficial effect for the combination of BA and SB (SMD = 0.32, 95% CI: 0.07; 0.57, p = 0.02, tau² = 0, tau = 0, I² = 0.0%). Meta-regression identified no differences between supplementing with BA or SB separately (F = 0.58; p = 0.57). Combining BA and SB improved exercise performance, however, there was no benefit in taking these supplements individually.